Osimertinib in Elderly Patients with Epidermal Growth Factor Receptor T790M‐Positive Non‐Small‐Cell Lung Cancer Who Progressed During Prior Treatment: A Phase II Trial - Nakao, Akira; Hiranuma, Osamu; Uchino, Junji; Sakaguchi, Chikara; Kita, Toshiyuki; Hiraoka, Noriya; Ishizuka, Tamotsu; Kubota, Yutaka; Kawasaki, Masayuki; Goto, Yasuhiro; Imai, Hisao; Hattori, Noboru; et al. (The oncologist (Dayton, Ohio), 2019)
Lessons Learned Non‐small‐cell lung cancer (NSCLC) represents 85% of lung cancer in elderly patients. In the present study performed in the 36 elderly subjects with epidermal growth factor receptor (EGFR) T790M mutation‐positive NSCLC, osimertinib 80 mg demonstrated statistically significant improvement in the objective response rate, which was comparable to those in the nonelderly population. Osimertinib appears to be an effective and safe treatment option in elderly patients with advanced NSCLC with EGFR mutation; further research in larger scale is warranted. Background Previous findings suggest the possibility of relatively safe use of osimertinib for patients with T790M‐positive non‐small‐cell lung cancer (NSCLC), with few serious adverse events for the elderly in comparison with conventional endothelial growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), and with an antitumor effect. Methods This phase II study was performed to prospectively investigate the efficacy and safety of osimertinib for elderly patients aged ≥75 years with ineffective prior EGFR TKI treatment or with recurrence in T790M EGFR TKI resistance mutation‐positive NSCLC. Results A total of 36 patients were included in the analyses. Among the 36 subjects, 63.9% were female, with mean age of 79.9 years. The objective response rate (ORR) was 58.3% (95% confidence interval [CI], 42.2%–72.9%), demonstrating statistically significant efficacy of osimertinib (p = .0017). The median duration of response (DOR) was 27.9 weeks (95% CI, 21.1–82.0). Complete response (CR) and partial response (PR) were 2.8% and 55.6%, respectively. Disease control rate (DCR) was 97.2%. A waterfall plot revealed that 33 (91.6%) subjects exhibited tumor shrinkage during treatment, including 12 of 14 subjects who had stable disease (SD). All adverse events were not reason for discontinuation of the study drug. Conclusion Osimertinib may be an effective and safe treatment option in elderly patients with advanced NSCLC with EGFR mutation. 经验获取 • 非小细胞肺癌 (NSCLC) 在老年患者肺癌中占 85%。 • 在本次于 36 名表皮生长因子受体 (EGFR) T790M 突变阳性 NSCLC 老年受试者中实施的研究中， 奥希替尼80 mg在客观缓解率方面展示出统计学方面的显著改善，这可以与非老年群体中的结果相媲美。 • 对于患有 EGFR 突变的晚期 NSCLC 老年患者，奥希替尼似乎是一种有效且安全的治疗方案；有必要进一步实施大规模研究。 摘要 背景。既往研究结果表明，在治疗 T790M‐阳性非小细胞肺癌 (NSCLC) 患者时可以相对安全地使用奥希替尼，与传统的表皮生长因子受体 (EGFR) 酪氨酸激酶抑制剂 (TKI) 相比，这种治疗方法在老年患者中产生的重度不良反应较少，且具有抗肿瘤效果。 方法。本次 II 期研究旨在前瞻性地调查奥希替尼在既往经 EGFR TKI 治疗无效或出现 T790M EGFR TKI 耐药性突变‐阳性 NSCLC 复发且年龄 ≥75 岁的老年患者中的疗效和安全性。 结果。一共有 36 名患者被纳入分析。在 36 名受试者中，63.9% 的患者为女性，平均年龄为 79.9 岁。客观缓解率 (ORR) 为 58.3% [95% 置信区间 (CI)，42.2%–72.9%]，显示出奥希替尼在统计学方面的显著疗效 (p = 0.001 7)。中位缓解持续时间 (DOR) 为 27.9 周(95% CI，21.1–82.0)。完全缓解 (CR) 和部分缓解 (PR) 分别为 2.8% 和 55.6%。疾病控制率 (DCR) 为 97.2%。据瀑布图显示，33 名受试者 (91.6%) 在治疗期间出现肿瘤退缩，包括 14 名受试者中的 12 名受试者出现疾病稳定 (SD)。所有不良反应均不是停用研究药物的原因。 结论。在患有 EGFR 突变的晚期 NSCLC 老年患者中，奥希替尼可能是一种有效且安全的治疗方案。